Disordered eating in three different age groups in Cyprus: a comparative cross-sectional study. (September 2018) - Hadjigeorgiou, Charalambos; Solea, Antonia; Querol, Sara Estecha; Keski-Rahkonen, Anna; Michels, Nathalie; Russo, Paola; Thumann, Barbara Franziska; Pala, Valeria; Danner, Unna
Abstract: Objective: The objective of this study was to evaluate disordered eating behaviours (DEBs) in different age groups in a Cypriot non-clinical population sample. Study design: Comparative cross-sectional study. Method: A total of 1716 participants from the Cyprus component of the I.Family study completed the Eating Attitudes Test-26 (EAT-26). The EAT-26 score ≥20 was used to define participants at risk for DEBs. Participants were divided according to age: adolescence (12–18 years old), young adulthood (25–45 years old) and middle adulthood (46–60 years old). Results: Mean EAT-26 total scores were higher for middle adulthood men and women compared with the two younger age groups. Young adulthood women had the highest percentage of behavioural symptoms of DEBs: binge eating (35%) and laxatives/diet pills/diuretics (12%) compared with the other age groups. Men and women in young adulthood had the highest percentage of participants with EAT-26 scores ≥20. In logistic regression analysis, age group did not prove a significant predictor of DEB risk in a model adjusting for sex, body mass index and physical activity. Conclusion: DEB can present at any age and was not confined to adolescence. Highlights: Disordered eating behaviours were assessed in three different age groups in a non-clinical population sample. Disordered eating attitudes were more frequent in young adulthood compared to adolescence and middle adulthood. Promotion of healthy eating behaviours, weight satisfaction and age-appropriate interventions are called for.